The effectiveness of holographic re-treatment on the meaning of life, fear of negative evaluation and rumination of depressed women - yaser rezapoor; maryam zakeri (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2019)
The purpose of present study was to investigate the effectiveness of holographic reprocessing therapy on the meaning in life, fear of negative evaluation and rumination of depressed women. This was a multiple baseline single-case study design. Tow depressed women who referred to social emergency center of Badroud city participated to the study and received 12 sessions holographic reprocessing therapy. Two weeks before the intervention, both of participants answer to meaning in life questionnaire (Steger & et al, 2006), fear of negative evaluation scale (Leary, 1983) and Ruminative response scale (Nolen-Hoeksema & Morrow, 1991). Also, the participants answered to thes questionnaire one day before the first session, as well as in the fourth, eighth and and twelfth intervention sessions and finally one month after the end of the sessions as follow up. The data were analyzed using graph analysis, improvement percentile rank and reliable change index. The findings showed that there were significant clinically and statistically improvement in The findings showed that there were significant clinically and statistically decrease in rumination of the participants after treatment. After two months of follow-up, differences were also maintained, indicating the sustainability of the therapeutic effects. According to the results, it can be concluded that holographic reprocessing therapy has significant effect on the meaning in life, fear of negative evaluation and rumination of depressed women was.